2012
DOI: 10.1097/igc.0b013e318232cab5
|View full text |Cite
|
Sign up to set email alerts
|

Province Wide Clinical Governance Network for Clinical Audit for Quality Improvement in Endometrial Cancer Management

Abstract: It is possible for a provincial oncology group to build an oncology network providing an improvement in the assistance of patients with endometrial cancer through the use of clinical audit. Clinical audit made it possible to obtain the full attendance of specialists of various disciplines involved in the treatment of endometrial cancer to optimize response time schematizing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…20,22 In endometrial cancer, prior studies mainly examined guideline adherence to surgical treatment recommendation or mixed with other malignancies, and no study has solely examined the association of patient noncompliance for postoperative radiotherapy and survival. [23][24][25][26][27][28][29] Our results of decreased survival in non-compliant women with endometrial cancer for postoperative radiotherapy are consistent with past studies reporting decreased survival related to non-compliance to radiotherapy shown in other malignancies. 6,7,29 Therefore, our study not only validates their results but also endorses that patient compliance for radiotherapy is an important factor for prognosis of women with endometrial cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…20,22 In endometrial cancer, prior studies mainly examined guideline adherence to surgical treatment recommendation or mixed with other malignancies, and no study has solely examined the association of patient noncompliance for postoperative radiotherapy and survival. [23][24][25][26][27][28][29] Our results of decreased survival in non-compliant women with endometrial cancer for postoperative radiotherapy are consistent with past studies reporting decreased survival related to non-compliance to radiotherapy shown in other malignancies. 6,7,29 Therefore, our study not only validates their results but also endorses that patient compliance for radiotherapy is an important factor for prognosis of women with endometrial cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Both the care provider‐side and the patient‐side can be factored for the guideline adherence, and these possible guideline adherent factors include hospital volume, patient medical comorbidities, and patient non‐compliance . In endometrial cancer, prior studies mainly examined guideline adherence to surgical treatment recommendation or mixed with other malignancies, and no study has solely examined the association of patient non‐compliance for postoperative radiotherapy and survival …”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were: inadequate EC treatment according to internal and international guidelines [ 20 , 21 ], neoadjuvant chemotherapy performed before surgery, an age less than 18 years, non-Caucasian ancestry, a follow-up length shorter than 6 months, inadequate follow-up according to internal guidelines, absence of written informed consent, diagnosis of a previous or concurrent cancer(s) and unavailable follow-up data.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were as follows: histological diagnosis of type II (non endometrioid tumors) EC, inadequate EC management according to internal and international guidelines [36,37], neoadjuvant chemotherapy performed before surgery, an age less than 18 years, nonCaucasian ancestry, a follow-up length shorter than 6 months, inadequate follow-up according to internal guidelines, absence of written informed consent, diagnosis of a previous or concurrent cancer(s), and unavailable follow-up data.…”
Section: Patient Samplesmentioning
confidence: 99%
“…Chemotherapy was administered to patients at stage III C and IV. In all cases, chemoradiotherapy consisted of paclitaxel 175 mg/m 2 (P) and carboplatin AUC5 (C) on day 1 every 3 weeks, for a total of four to six cycles, and it was followed by external pelvic radiation therapy (1.8 Gy/d, d1-5) at a total dose of 45 Gy plus vaginal brachytherapy (3×5 Gy) [36,38].…”
Section: Patient Samplesmentioning
confidence: 99%